A multifactor pricing model for cat bonds in the secondary market (2014)
Given the relevance that Cat Bonds are taking in the financial markets, as well as their appeal for different types of investors, it becomes pertinent to understand the price dynamics of these securities in the secondary market. Several authors have developed and proposed different valuation approaches, focusing on the probability of occurrence of catastrophic events, as the main variable impacting the pricing of Cat bonds in the secondary market. However, the lack of inclusion of other factors considered relevant for investors, narrows the range of pricing driver’s of Cat Bonds. This paper seeks to address the former need, presenting a panel data approach of a multifactor spread model, which comprehends 5 relevant variables. The results proved an adequate fitness and show that the model can be applied to both the P&C and, the Life market.